2015
DOI: 10.1155/2015/938594
|View full text |Cite
|
Sign up to set email alerts
|

Nanosuspension: An Emerging Trend for Bioavailability Enhancement of Etodolac

Abstract: Etodolac (ET) (poorly soluble drug) nanosuspensions were prepared by both pH shift method and antisolvent techniques in order to increase its dissolution rate. Various stabilizers were used, namely, Tween 20 and 80, HPMC, PVP K44, PVA, PEG 400, NaCMC, and -cyclodextrin. The prepared nanosuspensions were characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) and evaluated for their particle size, particle size distribution, and in vitro dissolution rate. In genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 50 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…It has been reported that a higher temperature can cause instability of the nanosuspensions, because the Brownian motion and kinetic energies of the suspended particles increase at an elevated temperature, which results in the aggregation and agglomeration of the particles. 64 Furthermore, at higher temperature, viscosity is decreased 80 and solubility of the suspended particles increases, which potentially leads to increase in interparticulate interaction, when particle growth can occur. For maximum stability of the nanosuspensions, Freitas and Müller 81 recommended storing the nanosuspensions at a temperature range of 2°C–8°C.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that a higher temperature can cause instability of the nanosuspensions, because the Brownian motion and kinetic energies of the suspended particles increase at an elevated temperature, which results in the aggregation and agglomeration of the particles. 64 Furthermore, at higher temperature, viscosity is decreased 80 and solubility of the suspended particles increases, which potentially leads to increase in interparticulate interaction, when particle growth can occur. For maximum stability of the nanosuspensions, Freitas and Müller 81 recommended storing the nanosuspensions at a temperature range of 2°C–8°C.…”
Section: Resultsmentioning
confidence: 99%
“…According to Figure 18, the increase of number of remaining homogenization cycle under 1500 bar also able to reduce the particle size proportionally. However, the particle size became slightly bigger with the increase of stabilizer:drug mass ratio instead of giving reduction effect which may due excessive envelop of stabilizer surround the drug particles (Afifi et al, 2015). In Figure 4, it shows that the increase of both homogenization pressure in first 10 cycles and number of remaining homogenization cycle under 1500 bar gave combination effect in the particle size reduction.…”
Section: Response Analysis and Response Surface Analysismentioning
confidence: 94%
“…CUR NS was prepared by the precipitation-high speed homogenization (HSH Ultraturrax T-25 IKA) method ( fig. 1) [6,7]. Briefly, a solution of the drug in the solvent was slowly introduced into antisolvent phase containing a surfactant, at 1:15 solvent: antisolvent ratio at homogenization speed of 10,000 rpm for 10 min.…”
Section: Preparation Of Nanosuspensionmentioning
confidence: 99%
“…Top-down technology involves the disintegration of larger particles into nanoparticles, examples of which are high-pressure homogenization and milling methods [6]. NS enhance solubility of drugs that are poorly water-soluble and poorly lipid soluble by increase in surface area following particle size reduction, increase in saturation solubility, increase in the time available for dissolution because of inherent adherence characteristics of nanoparticles to the gastrointestinal wall (high specific surface area being indicative of a high interactive potential with biological surfaces) [7].…”
Section: Introductionmentioning
confidence: 99%